Protracted Febrile Myalgia Syndrome: A Case Report Focusing on Possible Environmental Triggers - Mahmut ALPAYCI,; Arda KANDEMİR,; Mehmet KORKMAZ2, (Archives of Rheumatology, 2013)
Protracted febrile myalgia syndrome (PFMS) is an uncommon, dramatic manifestation of familial Mediterranean fever (FMF) which is characterized by severe myalgia and high fever. This syndrome is considered to be either a rare type of vasculitis requiring corticosteroid treatment or an extension of the inflammation in FMF which is associated with Mediterranean fever (MEFV) gene mutations. Although the exact environmental triggers for the syndrome are unknown, various factors, such as streptococcal infections, have been suggested. In this article, we present a 33-yearold male patient who developed PFMS after a long-term travel and hyperthermal (>40 °C) balneotherapy. To the best of our knowledge, this is the first case report which proposes a relationship between PFMS and balneotherapy.